Angiotensin–neprilysin inhibition confers renoprotection in rats with diabetes and hypertension by limiting podocyte injury. Issue 4 (April 2020) - Uijl, Estrellita; 't Hart, Daan C.; Roksnoer, Lodi C.W.; Groningen, Marian C. Clahsen-van; van Veghel, Richard; Garrelds, Ingrid M.; de Vries, René; van der Vlag, Johan; Zietse, Robert; Nijenhuis, Tom; Joles, Jaap A.; Hoorn, Ewout J.; et al.
Abstract : Objectives: Combined angiotensin receptor--neprilysin inhibition (ARNI) reduces glomerulosclerosis better than single angiotensin receptor blockade (ARB) in diabetic, hypertensive rats. The renoprotective mechanism remains unknown, but may depend on superior blood pressure control, improved renal hemodynamics, suppressed renal inflammation or prevention of podocyte loss. Methods: To address this, TGR(mREN2)27 rats (a model of angiotensin II-dependent hypertension) were made diabetic for 12 weeks and treated with vehicle ( n  = 10), valsartan (ARB; n  = 7) or sacubitril/valsartan (ARNI; n  = 8) for the final 3 weeks. Arterial pressure was measured via radiotelemetry. Results: Sacubitril/valsartan lowered mean arterial pressure by −50 ± 4 mmHg and valsartan by −43 ± 4 mmHg ( P  = 0.3). Both treatments lowered albuminuria, but only sacubitril/valsartan maintained high urinary atrial natriuretic peptide, improved glycemic control and protected podocyte integrity, reflected by increased nephrin expression and suppression of transient receptor potential canonical 6 and regulator of calcineurin 1. This resulted in markedly reduced glomerulosclerosis ( P  < 0.05 vs. control and valsartan). Despite higher effective renal plasma flow and glomerular filtration rates, sacubitril/valsartan did neither improve filtration fraction nor renal immune cell infiltration. Conclusion: Sacubitril/valsartan offers drug-class-specific renoprotection in a preclinical model of diabetes and hypertension. Renoprotection is unrelated to antihypertensive efficacy, renal hemodynamics or inflammation, but may be related to protective effects of natriuretic peptides on podocyte integrity. Abstract : Supplemental Digital Content is available in the text